Strong claims and weak evidence: reassessing the predictive validity of the IAT - Blanton, Hart; Jaccard, James; Klick, Jonathan; Mellers, Barbara; Mitchell, Gregory; Tetlock, Philip E (Journal of applied psychology, 2009)
The authors reanalyzed data from 2 influential studies-A. R. McConnell and J. M. Leibold and J. C. Ziegert and P. J. Hanges-that explore links between implicit bias and discriminatory behavior and that have been invoked to support strong claims about the predictive validity of the Implicit Association Test. In both of these studies, the inclusion of race Implicit Association Test scores in regression models reduced prediction errors by only tiny amounts, and Implicit Association Test scores did not permit prediction of individual-level behaviors. Furthermore, the results were not robust when the impact of rater reliability, statistical specifications, and/or outliers were taken into account, and reanalysis of A. R. McConnell & J. M. Leibold (2001) revealed a pattern of behavior consistent with a pro-Black behavioral bias, rather than the anti-Black bias suggested in the original study.